Analysis of Changes Model on Turnover Intention During the COVID-19 Pandemic - Jajang Supriatna; Djumarno Djumarno; Ahmad Badawy Saluy; Deden Kurniawan (Universitas Mercu Buana, 2022)
This study aimed to examine of changes model on turnover intention on the effect of job stress and organizational climate through job satisfaction in oil palm plantation companies during the COVID-19 pandemic. The analysis was conducted using 120 respondents comprising field and office employees identified in strategic positions as respondents. Data were collected using online questionnaires and tested for normality using Structural Equation Model (SEM) analysis with SmartPLS 3.2.7. The results showed that all the p-value indicators of the latent variable < 0.05 and this implies they are all valid and reliable to be used in the construct. The direct effects of X1 (JobStress) and X2 (Organizational Climate) on Y (Job Satisfaction), and X1 (Job Stress) on Z (Turnover Intention) were found to be significant while the other direct effects were insignificant. Moreover, all indirect effects were not significant but the effects of Total X1 (Job Stress) and X2 (Organizational Climate) on Y (Job Satisfaction) and the effect of X1 (Job Stress) on Z (Turnover Intention) were significant while the other total effects were insignificant. A strong indicator was discovered to be often thinking about leaving and actively looking for other job opportunities. This indicates that managers need to maintain work stress through the implementation of better policies related to work conditions. This is important because it was observed to affect job satisfaction, thereby, leading to turnover intention, especially during the COVID-19 pandemic.